THE GROWTH AND ANATOMICAL RESPONSE OF BLACK POTATO (PLECTRANTHUS ROTUNDIFOLIUS) TO FERMENTED COW, GOAT AND CHICKEN MANURE IN THE LOWLANDS - Ngadiani; Andriani, Vivin (jfpublisher, 2023)
Introduction. Food independence in Indonesia continues to be developed with other food crops to substitute the rice, one of it is by black potato. The productivity of lowland potato plants can be supported by the provision of nutrients. This research aims to determine the provision of fermented cow, goat and chicken manure on the growth, yield and anatomy of Black Potato Tubers (Plectranthus rotundifolius). Method. The method used was experimental with 12 treatments and repeated 3 times for each treatment, including control, 0 kg/plot, 5 kg/plot, 10 kg/plot, 15 kg/plot, and NPK. The parameters observed in this research were growth (plant height, number of leaves, number of branches) and anatomy (diameter of stems and stomatal density). Results and Analysis. The data were analyzed using Anova test with a significance of α = 0.05, and the difference test is conducted using Duncan when there is a difference in the test result. Discussion. The results showed that chicken manure had a better effect on the growth and anatomy of black potato plants compared to goat manure and cow manure.